Pengaruh Fleksibilitas Kerja Terhadap Keseimbangan Hidup Generasi Z - Kusumaningrum, Arini; Yacub, Rudi; Prihantoro, Kasih; Dadi Priadi, Muhammad; Herlina, Herlina (PDPI, 2025)
This study aims to find out and analyze the influence of work flexibility on the work-life balance of generation Z. The phenomenon of increasing the number of workers from generation Z who demand freedom in time management and workplace is an important background for this research. The approach used is quantitative with the survey method. Data was collected through the distribution of questionnaires to Generation Z respondents who have worked in various industrial sectors, then analyzed using simple linear regression analysis to test the influence of independent variables on dependent variables. The results of the study show that work flexibility has a positive and significant effect on the life balance of generation Z. This means that the higher the level of flexibility provided by the company both in terms of time, location, and work system the better the balance between personal and work life felt by generation Z employees. young people in the environment of modern organizations.